2023
DOI: 10.1038/s41598-022-26298-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analyses of pseudoscorpions in a subterranean biodiversity hotspot reveal cryptic diversity and microendemism

Abstract: Nested within the Mediterranean biodiversity hotspot, the Dinaric Karst of the western Balkans is one of the world’s most heterogeneous subterranean ecosystems and renowned for its highly diverse and mostly endemic fauna. The evolutionary processes leading to both endemism and diversity remain insufficiently understood, and large-scale analyses on taxa that are abundant in both subterranean and surface habitats remain infrequent. Here, we provide the first comprehensive molecular study on Croatian pseudoscorpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…Fragments of one mitochondrial and two nuclear genes were sequenced using standard Sanger methodology for this study and these sequences have proven to be useful in reconstructing pseudoscorpion phylogeny in a range of different taxa (Murienne et al 2008;Harvey et al 2015Harvey et al , 2016aHarvey et al , 2016bHarvey et al , 2020Harms et al 2019;Johnson et al 2022;Hlebec et al 2023). The present study included fragments of the cytochrome c oxidase subunit I (COI), 18S ribosomal RNA (18S) and 28S ribosomal RNA (28S).…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Fragments of one mitochondrial and two nuclear genes were sequenced using standard Sanger methodology for this study and these sequences have proven to be useful in reconstructing pseudoscorpion phylogeny in a range of different taxa (Murienne et al 2008;Harvey et al 2015Harvey et al , 2016aHarvey et al , 2016bHarvey et al , 2020Harms et al 2019;Johnson et al 2022;Hlebec et al 2023). The present study included fragments of the cytochrome c oxidase subunit I (COI), 18S ribosomal RNA (18S) and 28S ribosomal RNA (28S).…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Only two species of Verhoeffiella are listed for the whole system [12] (Figure 6D), although more species belonging to different genera and even families are known from it (Lukić M., personal communication). Finally, numbers might further increase by identification of morphologically cryptic species, which are repeatedly identified among specialized subterranean taxa, including Dinaric collembolans [101][102][103].…”
Section: General Overview and Significance Of The New Species Listmentioning
confidence: 99%
“…There is growing evidence that even in central Europe, a region with a long tradition of faunistic and taxonomic research [17], the true species diversity of pseudoscorpions is not even roughly known. Studies involving DNA barcoding have demonstrated that currently accepted species often constitute complexes of cryptic species [15,[18][19][20]. This was most obvious in non-vagile, soil-dwelling representatives (Chthoniidae, Neobisiidae), with Neobisium carcinoides (Hermann, 1804) being the most prominent example.…”
Section: Introductionmentioning
confidence: 99%